Hubungan Patient Handling Dengan Kejadian Musculoskeletal Disorders Pada Perawat Di Rsu Pku Muhammadiyah Delanggu - Maysyaroh, Nuriana Dessy, Dr. Suwaji, M.Kes (2016)
Nurses are health workers in hospitals with work activities are quite varied and heavy in terms of handling patients ranging from activities to lift, push, pull, reach out and bring. Musculoskeletal disorders is one of the occupational diseases that commonly occur in nursing. The purpose of this research was to know the relationship of riks by patient handling with the incidence of musculoskeletal disorders in nurses at RSU PKU Muhammadiyah Delanggu. This research method research design analytic survey with cross sectional approach. Subject of the study were 62 nurses using purposive sampling. Measurement of patient handling using RULA and measurement of musculoskeletal disorders using the NBM. Data analysis using test statistics Chi Square. Statistical test results for patient handling relations with the incidence of musculoskeletal disorders is obtained value of p = 0.048. The conclusion of this study stated that there is a significant between the risk of patient handling with the incidence of musculoskeletal disorders in nurses at RSU PKU Muhammadiyah Delanggu